Physicochemical and sensory characterization of okara obtained by two different processes and the study of its use as breaded food - KNIAZEV, Maximiliano; GÁMBARO, Adriana; VIEITEZ, Ignacio (Food Science and Technology, 2023)
Soybean residue, known as okara, is a byproduct of soymilk production with varying compositions based on the production process. This study explored the characteristics of fresh and dried, disc-milled, and all-metal hammer-milled okara derived from soy crops in Uruguay through different techniques, including physicochemical, microbiological, and sensory analyses. Specifically, dried disc-milled okara was used in making breaded tofu steak, and the sensory traits and oil absorption of the fried product were examined when bread crumbs were substituted with okara in proportions of 0, 25, 50, 75, and 100%. The production process affected moisture, protein, fiber, and oxidative rancidity. Dried samples showed differences in smell, crispness, and particle size, while the drying process reduced microbial load and total polyphenols but enhanced lightness, redness, and yellowness. All samples exhibited a similar fatty acid profile, mainly C18:2. Increasing okara content in breading enhanced the color and smell of fried steaks. Interestingly, there was no significant difference in fat content between the 0 and 100% okara substitutions. This study concludes that dried okara, rich in fiber, protein, and essential fatty acids, presents potential as a functional food for human consumption. It also serves as a sustainable and nutritious breading substitute, offering an alternative to conventional ingredients.